1998
DOI: 10.1023/a:1024413301064
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behavior after severe trauma. Part 2: The association between methods of torture and of suicidal ideation in posttraumatic stress disotrder

Abstract: The study reports on 65 refugees with diagnoses of posttraumatic stress disorder (PTSD) and manifest suicidal behavior (40% had suicide attempts; 29% detailed suicide plan; 31% recurrent suicidal thoughts). Our hypothesis was that the predominant kind of stressful experience in PTSD patients might be reflected in their choice of method when pondering or attempting suicide. Relationships were found to exist between the main stressors and the respective subjects' preference for suicide method. Particularly among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 16 publications
1
34
0
1
Order By: Relevance
“…Within the larger study from which the current research project was drawn, those Bhutanese refugees who had experienced their house or shelter being burned down had 4 times greater odds of reporting suicidal ideation (Ao et al, 2012). Ferrada-Noli, Asberg, and Ormstad (1998) found a high incident rate of suicide attempts (40%) among refugees with PTSD. Furthermore, in a study of refugees who were also torture-survivors, Ferrada-Noli Asberg, Ormstad, Lundin, & Sundbom, (1998) found that the method of torture corresponded to the suicidal ideation or attempt method, for example, water torture and drowning.…”
Section: Perceived Burdensomeness Thwarted Belongingness and The Rementioning
confidence: 95%
“…Within the larger study from which the current research project was drawn, those Bhutanese refugees who had experienced their house or shelter being burned down had 4 times greater odds of reporting suicidal ideation (Ao et al, 2012). Ferrada-Noli, Asberg, and Ormstad (1998) found a high incident rate of suicide attempts (40%) among refugees with PTSD. Furthermore, in a study of refugees who were also torture-survivors, Ferrada-Noli Asberg, Ormstad, Lundin, & Sundbom, (1998) found that the method of torture corresponded to the suicidal ideation or attempt method, for example, water torture and drowning.…”
Section: Perceived Burdensomeness Thwarted Belongingness and The Rementioning
confidence: 95%
“…A study of psychiatric morbidity due to war in northern Sri Lanka found that 38% of individuals subjected to torture had suicidal ideation. 78 FerradaNoli et al, 30,79 in a study of traumatized refugees in Sweden, found that 40% of individuals with a diagnosis of PTSD had attempted suicide at least once and that comorbid depression was a risk factor for their suicidal behavior.…”
Section: Torturementioning
confidence: 99%
“…Human rights abuses, especially those related to forms of violence, have been found to be associated with poor mental health, particularly post traumatic stress disorders (Kaminer et al, 2008; Norris et al, 2003; Creamer et al, 2001). Suicidal thoughts and behaviors have been found to be highly related to partner violence among women (Ellsberg et al, 2008) and among refugees who have been exposed to torture (Ferrada- Noli et al, 1998). Although most studies report that it was difficult to definitively establish causes of suicide, the strength of the associations suggested that mental health could be an outcome of abuse rather than a precursor of abuse (Ellsberg at al, 2008).…”
Section: Introductionmentioning
confidence: 99%